Occurrence of patulin and 5-hydroxymethylfurfural in apple sour, which is a traditional product of Kastamonu, Turkey - İçli, Nesrin (Informa UK Limited, 2019)
Apple sour is a traditional product of Kastamonu, Turkey. It is consumed by spreading on bread or drinking after diluting with water. The aim of this study was to determine patulin (PAT) and 5-hydroxymethylfurfural (HMF) in apple sour. This study is the first to evaluate the occurrence of PAT and HMF in apple sour. The samples were extracted with ethyl acetate using liquid-liquid extraction technique. PAT and HMF were determined by HPLC with UV detection. PAT was detected in all samples, and the PAT level in 94.9% of samples was found to be equal or greater than the legal limit for juice concentrates. The mean value for PAT was found to be 284 ± 307 μg kg-1. PAT levels in 13 of 39 samples were in the range of 100 ≤ x < 200 μg kg-1, two samples were in the range of 0 ≤ x < 50 μg kg -1 and two samples were in the range of 1000 ≤ x < 1500 μg kg1. HMF levels of all samples were above the legal limit for solid molasses. The mean value for HMF was found to be 16215 ± 13317 mg kg-1. HMF levels of 10 of 39 samples were determined to be in the range of 10000 ≤ x < 20000 mg kg-1, eight samples were in the range of 20000 ≤ x < 30000 mg kg-1 and only three samples were in the range of 100 ≤ x < 1000 mg kg-1. There was a significant and inverse relationship between HMF and pH of the samples. These results indicate that consumption of apple sour is a considerable risk in terms of HMF and PAT toxicity.
Keywords: Beverages; Patulin; Turkey; Malus; Food Contamination; Furaldehyde